2008
DOI: 10.1177/0269215508095357
|View full text |Cite
|
Sign up to set email alerts
|

The effect of additional strengthening of hip abductor and lateral rotator muscles in patellofemoral pain syndrome: a randomized controlled pilot study

Abstract: Supplementation of strengthening of hip abductor and lateral rotator muscles in a strengthening quadriceps exercise programme provided additional benefits with respect to the perceived pain symptoms during functional activities in patients with patellofemoral pain syndrome after six weeks of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
228
2
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(254 citation statements)
references
References 31 publications
8
228
2
16
Order By: Relevance
“…3,23,44 Limited research on the efficacy of isolated hip strengthening has provided evidence of improvements in pain, function, and strength in this population. 31,34 The presence of multiple effective interventions creates a dilemma for clinicians treating patients with PFPS. It is unclear whether initial hip or quadriceps strengthening will better prepare patients for more functional lower extremity exercises, particularly if functional activities cannot be initiated immediately or are not initially tolerated in some patients.…”
Section: T T Conclusionmentioning
confidence: 99%
“…3,23,44 Limited research on the efficacy of isolated hip strengthening has provided evidence of improvements in pain, function, and strength in this population. 31,34 The presence of multiple effective interventions creates a dilemma for clinicians treating patients with PFPS. It is unclear whether initial hip or quadriceps strengthening will better prepare patients for more functional lower extremity exercises, particularly if functional activities cannot be initiated immediately or are not initially tolerated in some patients.…”
Section: T T Conclusionmentioning
confidence: 99%
“…2,4,7,19,39,40 Thus hip strengthening is often advocated to improve hip mechanics, 26 with the intent of reducing the incidence of, or symptoms related to, PFPS. 4,15,19,27,28 Although it has been shown that these programs improve strength 3,23,28 and reduce or might prevent symptoms, 3,15,21,23,28 it is not clear whether strengthening the hip actually results in improvement of abnormal hip and knee mechanics during functional activities such as running and squatting. …”
mentioning
confidence: 99%
“…www.casp-uk.net Beneficial effect of hip exercise in PFP Baldon et al, 2014Coppack et al, 2011Ferber et al, 2014Fukuda et al, 2010Fukuda et al, 2012Ismail et al,2013Nakagawa et al, 2008Dolak et al, 2011Khayambashi et al, 2012Avraham et al, 2007Boling et al, 2006Earl & Hoch 2011Ferber et al, 2011Khayambashi et al, 2014Lowry et al, 2008Mascal et al,2003Noehren et al .,2011Razheghi et al, 2010Tyler et al,2006Willy et al, 2012 No benefit of hip exercise in PFP Song et al, 2009 www.cebm.net/ocebm-levels-of-evidence…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Step-up Wall-squat Nakagawa et al, 2008 Step-up Wall slide Additionside -ly OKC abd Forward lunge Addition side-ly OKC abd, pelvic drop…”
Section: Pelvic Drop Single Leg Deadliftmentioning
confidence: 99%